Contributions to Reductional Archaeology. The case of Nuestra Señora de Ibitiracuá (Concepción de la Sierra, Misiones, Argentina) - Ocampo, Amanda E.; Richard, Alejandro; Sastre, Yamila; Candelario, Soledad (Instituto de Arqueología, Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2019)
In this paper, we discuss the data obtained from archaeological studies in Concepción de la Sierra historical center (Misiones, Argentina), the former location of Nuestra Señora de Ibitiracuá Jesuit-Guarani reduction. We present the preliminary analysis of the material evidence recovered from several test pits, and compare the results with previous regional data from the pre- and post- Hispanic periods. We analyze the formal attributes of the recovered material in order to identify the features preserved on sub-surface materials, in spite of the archaeological context high dynamism and disturbance. So far, the evidence supports the periodicity of the different historical periods and the continuity of some pre-Hispanic ceramic styles. Finally, we address the high degree of material and spatial reuse in this and other reductions in Misiones Province. We also argue for our discipline role in protecting living, dynamic heritage sites increasingly threatened by urbanization.